1998
DOI: 10.1172/jci620
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of leukotriene C4 synthase in bronchial biopsies from patients with aspirin-intolerant asthma.

Abstract: Aspirin causes bronchoconstriction in aspirin-intolerant asthma (AIA) patients by triggering cysteinyl-leukotriene (cys-LT) production, probably by removing PGE2-dependent inhibition. To investigate why aspirin does not cause bronchoconstriction in all individuals, we immunostained enzymes of the leukotriene and prostanoid pathways in bronchial biopsies from AIA patients, aspirin-tolerant asthma (ATA) patients, and normal (N) subjects. Counts of cells expressing the terminal enzyme for cys-LT synthesis, LTC4 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
422
4
18

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(468 citation statements)
references
References 69 publications
(93 reference statements)
24
422
4
18
Order By: Relevance
“…In humans, it has been suggested that increased production of cysteinyl-LT correlates with susceptibility to aspirin-intolerant asthma (37,38). Recent studies have shown that variations in the synthesis of cysteinyl-LT result from a polymorphism in the LTC 4 synthase gene promoter, which causes constitutive overexpression of this enzyme in aspirin-sensitive patients (37)(38)(39)(40). Differing expression levels of LTC 4 synthase may account for variability observed in the response to LT inhibitors used in the treatment of asthma (37).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it has been suggested that increased production of cysteinyl-LT correlates with susceptibility to aspirin-intolerant asthma (37,38). Recent studies have shown that variations in the synthesis of cysteinyl-LT result from a polymorphism in the LTC 4 synthase gene promoter, which causes constitutive overexpression of this enzyme in aspirin-sensitive patients (37)(38)(39)(40). Differing expression levels of LTC 4 synthase may account for variability observed in the response to LT inhibitors used in the treatment of asthma (37).…”
Section: Discussionmentioning
confidence: 99%
“…Ptges −/− mice develop marked eosinophildominated bronchovascular cellular infiltrates (>75% of BAL fluid cells) with lesser numbers of neutrophils (28,35). AERD is also associated with marked eosinophilia of the respiratory mucosa (44), often without evidence of sensitization to allergens. Because there is no method to elicit eosinophilic inflammation in mice independently of allergen, we elicited eosinophilic pulmonary inflammation in WT and ptges −/− mice with Df and challenged with Lys-ASA to determine whether impaired inducible PGE 2 generation permitted AERD-like physiology.…”
Section: Deletion Of Hematopoietic Ep 2 Receptors Partially Reproducementioning
confidence: 99%
“…The comparatively modest effect of anti-IL-5 may reflect incomplete depletion of eosinophils from the airway (as described in humans with asthma) (57). Alternatively, eosinophils may contribute to baseline cysLT generation (44), whereas other cells provide cysLTs during the reaction.…”
Section: Deletion Of Hematopoietic Ep 2 Receptors Partially Reproducementioning
confidence: 99%
“…However, we found no significant associations between the phenotype of AIA and these two polymorphisms or their haplotypes in this study, and no significant differences were noted with other clinical parameters. It has been reported that LTC4S was expressed five times more strongly in bronchial biopsies from AIA patients compared to ATA and normal controls (Cowburn et al 1998). Sanak et al (1997Sanak et al ( , 2000 showed that AIA was associated with the genetic polymorphism of LTC4S -444A>C, which has an additional responsive element to histone H4 transcription factor-2, and increases the transcription rate of the gene in vitro and in vivo in a Polish population.…”
Section: Discussionmentioning
confidence: 98%